2020
DOI: 10.3390/mi11040377
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Drilling of Sapphire Using Electro Chemical Discharge Machining

Abstract: Electrochemical discharge machining (ECDM) refers to a non-traditional machining method for performing effective material removal on non-conductive hard and brittle materials. To increase the ECDM machining efficiency, traditionally, the method of increasing the machining voltage or increasing the electrolyte concentration is used. These methods can also cause overcut reaming of the drilled holes and a rough surface on the heat affected area. In this study, an innovative combinational machining assisted method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…These include modifying the tool shape, including using flat sidewall-flat front tool [7], side-insulated tool [8], drill bit [9], helical tool with high-speed rotation [10], internally structured tube electrode [11] and spherical tip tool [12]. Other attempts include using pulsed voltage [13,14], modifying the electrolyte constituents [15,16], adding tool motion such as rotation [17] and orbital motion [18], adding tool vibration [19], vibrating electrolyte [20] and doing magnetic assisted field machining [21,22]. It was also shown that deeper holes could be established through adding pressurized electrolyte flow [23] and by applying counter-resistant feeding through reducing the magnitude of contact force between the tool and substrate as drilling progresses [24].…”
Section: Introductionmentioning
confidence: 99%
“…These include modifying the tool shape, including using flat sidewall-flat front tool [7], side-insulated tool [8], drill bit [9], helical tool with high-speed rotation [10], internally structured tube electrode [11] and spherical tip tool [12]. Other attempts include using pulsed voltage [13,14], modifying the electrolyte constituents [15,16], adding tool motion such as rotation [17] and orbital motion [18], adding tool vibration [19], vibrating electrolyte [20] and doing magnetic assisted field machining [21,22]. It was also shown that deeper holes could be established through adding pressurized electrolyte flow [23] and by applying counter-resistant feeding through reducing the magnitude of contact force between the tool and substrate as drilling progresses [24].…”
Section: Introductionmentioning
confidence: 99%